The pastor as scholar and the scholar as pastor : reflections on life and ministry - Piper, John, 1946-; Carson, D. A.; Mathis, David, 1980-; Strachan, Owen. (Wheaton, Ill. : Crossway, 2011)
"Dr. D.A. Carson beautifully blends his love for pastoral ministry and scholarship in a series of short arguments. Like Piper, he shares his journey and the 'providential twists' that have contributed to his life as a scholar. Most helpful are the lessons that Carson sets forth for the scholar as pastor. He encourages scholars to guard against an ivory tower mentality. As such, the encouragement includes immersion in the real world. Carson encourages scholars to steer clear from the deadly 'seduction of applause' which may come from publishing house and wide readership as well as a close circle of friends...the author encourages scholars to fight what he calls a 'common disjunction' between the 'objective study of Scripture and devotional reading.' Of course, he encourages scholars to critically engage with the text, but he also encourages meaningful times of devotion. Scholars must tremble before God's Word (Isa. 66:2)...[In] a fitting conclusion, David Mathis points readers to Jesus, the supreme example of a pastor-scholar: 'Jesus, the God-man, is the ultimate model of engaging both heart and head, not compromising either for the other.' This indeed is the aim of the editors, namely, for scholarship and pastoral ministry to point to Jesus and his gospel.The Pastor as Scholar and the Scholar as Pastor is a refreshing and liberating book, especially for any pastor who takes scholarship seriously. For pastors who have grown weary of scholarship and have pushed the hard work of exegesis to the margins of their ministry - this book will be a challenging, yet helpful antidote that will benefit not only the pastor, but the people he is called to shepherd" -- Amazon.com.
Introduction: the return of the pastor-scholar / Owen Strachan -- The pastor as scholar: a personal journey and the joyful place of scholarship / John Piper -- The scholar as pastor: lessons from the church and the academy / D. A. Carson -- Conclusion: the preacher, the professor, and the true pastor-scholar / David Mathis.
Includes bibliographical references and index.
Keywords: Pastoral theology; Theology -- Study and teaching; Clergy -- Post-ordination training